From Tecún Umán to the new América. Martí and the mayar culture of Guatemala. - Rodríguez, Pedro Pablo (2019)
José Martí (1853-1895), the Apostle of Cuban independence, was an admirer the Mayan culture. This admiration was forged through knowledge of archaeological evidence, the historical and anthropological studies from his time, and by his personal contacts with Maya peoples and communities during his residence in Guatemala in1877 and 1878. That knowledge drove his of view that the culture of Nuestra América [Our America], like that of other pre-Hispanic peoples, was essential to forge nations far removed from all colonial backwardness.